Impact of proactive malaria community case management (proCCM) on parasite prevalence and incidence from 2021 to 2023: a randomised controlled trial in Chadiza District, Eastern Province, Zambia - Adam Bennett; Busiku Hamainza; Marie-Reine I Rutagwera; Ellen L Ferriss; Bupe M Kabamba; Travis Porter; Chabu C Kangale; Sarah Gallalee; Melody Simataa; John M Miller; Caroline Phiri-Chibawe; Maximillian Musunse; et al. (BMJ Global Health)
Ensuring prompt and effective case management of malaria remains an ongoing challenge in Zambia, where care is not sought for roughly 40% of febrile children under 5 years of age. To expand access, the Ministry of Health has scaled up routine malaria community case management (mCCM) for all ages over the past decade. As of 2018, nearly a quarter of children who received antimalarials obtained them from a community health worker (CHW), but gaps in treatment seeking remain. Proactive community case management (proCCM), under which CHWs regularly visit households to screen, test and treat individuals for malaria, aims to improve timely case management, avert severe disease and potentially reduce transmission. To evaluate the impact of weekly proCCM on malaria parasite prevalence and incidence in the context of strong routine community case management, we conducted a two-arm cluster-randomised controlled trial, comparing proCCM plus routine passive care to routine passive care only in Chadiza District, Eastern Province, Zambia, between April 2021 and May 2023. Baseline and endline surveys were conducted during peak transmission season to ascertain parasite prevalence, while facility, routine mCCM and proCCM incidence data were collected through routine surveillance systems and weekly household visits, respectively. In the control arm, malaria prevalence decreased from 19.7% in 2021 to 16.0% in 2023, and in the intervention arm, from 18.7% to 13.7%. No significant difference between arms in the change in parasite prevalence was estimated (adjusted relative risk=0.97, 95% CI=0.77 to 1.23). However, there was a small, ongoing decline in malaria incidence each month in proCCM clusters compared with control clusters (adjusted incidence rate ratio=0.98, 95% Bayesian credible interval=0.96 to 0.99). Our study suggests proCCM may modestly reduce malaria incidence over time in some settings with high baseline utilisation of routine facility and community case management. Trial registration number: NCT04839900